Shark and ray research in India has low relevance to their conservation - Gupta, T; Karnad, D; Kottillil, S; Kottillil, S; Milner-Gulland, EJ (Elsevier, 2021)
With global biodiversity currently facing unprecedented losses, it is critical that resources are allocated and used effectively to mitigate these threats, especially in resource-limited tropical countries of the global south. Chondrichthyans (sharks, rays and chimaeras) are particularly threatened by overexploitation, with India being amongst the top fishing nations for these species and a priority region for their conservation. We conducted a scoping review of chondrichthyan literature in India to assess the relevance of this research to the conservation of these threatened species. Between March and April 2021, we searched for peer reviewed and grey literature across national and international databases and found 482 chondrichthyan publications. While the number of publications exponentially increased with time, the literature is dominated by short-term fisheries studies, biological records and observations, with less than 10% of studies addressing socio-economic and management themes. Research was biased towards specific states, particularly Tamil Nadu and Kerala, and towards charismatic species like the whale shark, leading to under-representation of potentially important regions and taxa. Overall, our study found low relevance and applicability of India's research literature to chondrichthyan conservation. There is a need for more directed and applied research explicitly aimed at informing conservation. We highlight specific data gaps, such as the need for improved understanding of the socio-economic aspects of chondrichthyan fisheries, species risk assessments at the regional level, data on critical habitats, and the evaluation of existing policies. Addressing these gaps can help ensure that effort is allocated to the regions, species and topics that need it the most, for improved conservation outcomes.